Light As a Metaphor of Consciousness: Integrating Suhrawardi’s Illuminationist Philosophy and Modern Psychology - Aliana, Cut Rizka; Firdaus; Soraya; Syamsul Rijal (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2025)
This study explores light as a metaphor for consciousness by integrating Suhrawardi’s philosophy of illumination with modern psychology. In Suhrawardi’s view, light is not only a metaphysical symbol but an ontological reality linking human beings to the divine source of knowledge. Meanwhile, modern psychology examines consciousness through neurocognitive, cognitive, and phenomenological perspectives. Using a qualitative library-based method and philosophical hermeneutics, this research identifies areas of convergence and divergence between the two approaches. The findings reveal that Suhrawardi’s gradation of light offers a framework for understanding consciousness as a multilayered spiritual process rather than merely a biological phenomenon. This concept parallels modern psychology’s notions of self-actualization and peak experience. The integration of these perspectives provides valuable insights for developing spirituality-based psychotherapy, Islamic counseling, and consciousness education in Indonesia, highlighting the relevance of Islamic intellectual traditions to contemporary psychological discourse. Keywords: Consciousness, Illumination, Modern Psychology, Light, Suhrawardi